Eleanor Sweeney - Thesis submitted in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology (DClinPsych) - Sweeney, E (2023)
Systematic literature review: Are school-based interventions to prevent teen dating violence theory-driven, and are they effective? A systematic literature review